Quo vadis? Central Rules of Pathogen and Disease Tropism - McCall, Laura-Isobel (Frontiers in Cellular and Infection Microbiology, 2021)
Understanding why certain people get sick and die while others recover or never became ill is a fundamental question in biomedical research. A key determinant of this process is pathogen and disease tropism: the locations that become infected (pathogen tropism), and the locations that become damaged (disease tropism). Identifying the factors that regulate tropism is essential to understand disease processes, but also to drive the development of new interventions. This review intersects research from across infectious diseases to define the central mediators of disease and pathogen tropism. This review also highlights methods of study, and translational implications. Overall, tropism is a central but under-appreciated aspect of infection pathogenesis which should be at the forefront when considering the development of new methods of intervention.